Knowledge Sharing Organizational Justice And Commitment In Employee Performance: Pembagian Pengetahuan, Keadilan Organisasi, dan Komitmen dalam Kinerja Karyawan - Ody Mahardika; Rifdah Abadiyah (Indonesian Journal of Law and Economics Review, 2025)
General Background Human resource management emphasizes employee performance as a key organizational outcome. Specific Background Within this context, knowledge sharing and organizational justice are frequently associated with performance through organizational commitment. Knowledge Gap Previous studies report inconsistent findings regarding the mediating role of organizational commitment. Aims This study examines the relationships between knowledge sharing, organizational justice, employee performance, and organizational commitment at PT. Panggung Electric Citrabuana. Results Using quantitative analysis with SEM-PLS on data from 80 employees, the findings indicate that knowledge sharing is associated with employee performance, organizational justice is associated with organizational commitment, and organizational commitment is associated with employee performance, while organizational justice shows no direct association with employee performance and knowledge sharing shows no association with organizational commitment. Novelty The study clarifies the selective mediating role of organizational commitment within the examined relationships in a manufacturing context. Implications These findings provide empirical insights for organizational management in structuring internal knowledge practices and fairness perceptions to support employee performance. Keywords: Knowledge Sharing, Organizational Justice, Organizational Commitment, Employee Performance, Human Resource Management Key Findings Highlights: Knowledge exchange within the organization aligns with employee output outcomes Fairness perceptions strengthen internal attachment to the organization Internal attachment functions as a pathway linking fairness and work results